Low circulating androgens and mortality risk in heart failure. Issue 7 (28th October 2009) - Güder, G; Frantz, S; Bauersachs, J; Allolio, B; Ertl, G; Angermann, C E; Störk, S
Abstract : Objective: Deficiency of anabolic sex steroids is common in heart failure (HF). The pathophysiological implications of this phenomenon, however, have not been fully elucidated. This clinical study investigated the significance of low serum androgen levels in HF. Design: Prospective cohort study. Patients and Methods: In 191 consecutively recruited men with HF (mean age 64 years; New York Heart Association (NYHA) class I–IV 24%/35%/35%/6%) and reduced (ejection fraction (EF) ≤40%, n=96) or preserved (EF >40%, n=95) left ventricular function total and free serum testosterone, dehydroepiandrosterone sulfate (DHEAS) and sex hormone binding globulin (SHBG) were measured. The median observation period was 859 days. Results: During follow-up 53 patients (28%) died. Whereas total serum testosterone was normal in most patients (91%), free testosterone and DHEAS were reduced in 79% and 23%, respectively. DHEAS and free testosterone, but not total testosterone, were inversely associated with NYHA class (both p<0.01). Lower free testosterone and DHEAS and higher SHBG predicted all-cause mortality risk (hazard ratio (HR) 0.89, 95% CI 0.82 to 0.96 per 1 ng/dl free testosterone, p=0.004; HR 0.95, 95% CI 0.89 to 1.00 per 10 μg/dl DHEAS, p=0.058; and HR 1.18, 95% CI 1.05 to 1.33 per 10 nmol/l SHBG, p=0.006, respectively; adjusted for age and NYHA class). However, further adjustment for carefully selected confounding factors abolished these associations. Conclusion: In male HF patients, low serum levels of androgens are associated with adverse prognosis, but this relation is confounded by indicators of a poor health state. The results suggest that low serum androgens develop as a sequel of this progressive multifaceted systemic disorder.